Tunable Probes with Direct Fluorescence Signals for the Constitutive and Immunoproteasome. Issue 42 (6th October 2016) - Dubiella, Christian; Cui, Haissi; Groll, Michael
Abstract: Electrophiles are commonly used for the inhibition of proteases. Notably, inhibitors of the proteasome, a central determinant of cellular survival and a target of several FDA‐approved drugs, are mainly characterized by the reactivity of their electrophilic head groups. We aimed to tune the inhibitory strength of peptidic sulfonate esters by varying the leaving groups. Indeed, proteasome inhibition correlated well with the p K a of the leaving group. The use of fluorophores as leaving groups enabled us to design probes that release a stoichiometric fluorescence signal upon reaction, thereby directly linking proteasome inactivation to the readout. This principle could be applicable to other sulfonyl fluoride based inhibitors and allows the design of sensitive probes for enzymatic studies. Abstract : A tunable light : The potency of peptidic sulfonate esters as proteasome inhibitors can be fine‐tuned by altering the p K a of the leaving group. The introduction of a fluorescent dye as a leaving group allows direct monitoring of proteasomal activity and can be used for quantification. This concept might inspire future work on other hydrolases.